Test and evaluation of aircraft avionics and weapon systems - McShea, Robert E. (SciTech Pub. ; American Institute of Aeronautics and Astronautics, 2010)
The book reviews developments in the following fields: avionics; time, space, and position information; digital data busses; data reduction; data analysis; MIL-STD-1553; communications flight test; navigation systems; avionics civil certifications; electro-optical systems; infrared systems; radio detection; ranging; radar; electronic warfare; and weapons integration.
Keywords: Flight testing.; Airplanes -- Flight testing.; Airplanes, Military -- Flight testing.; Weapons systems -- Testing.; Avionics -- Testing.; Airplanes, Military -- Armament -- Testing.; elektronické knihy; electronic books